Pemberdayaan Masyarakat melalui Maggotisasi dalam Pengelolaan Sampah Organik dan Pemanfaatannya sebagai Pakan Ikan di Dusun Gatak, Bantul - Audrey Nainggolan; Habibie Erlangga Putra; Farsya Auliya Z; Permata Setia Ayusdini; Heru Subaris Kasjono; Ibnu Rois (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2024)
The increasing volume of organic waste in Bantul Regency has become a critical environmental and public health issue, particularly due to the limited capacity of the Piyungan Integrated Waste Processing Site (TPST). This condition has led to waste accumulation at the community level, including in Dusun Gatak, posing risks to environmental quality and public health. This community service program aimed to enhance community capacity in managing organic waste through a maggot-based approach using community empowerment strategies. The intervention employed a participatory community empowerment model, consisting of initial engagement, Community Self Survey (CSS), training, and mentoring stages. The target participants included local residents, community cadres, youth organizations, and fish farming groups. Evaluation was conducted using pre-test and post-test assessments as well as participatory observation. The results showed a CSS response rate of 66%, indicating that most households had not yet managed organic waste effectively. The training program significantly improved participants’ knowledge, as reflected by an increase in average scores from 60 to 85. Maggot-based waste processing was selected as the preferred method due to its practicality and economic potential as an alternative fish feed. Initial implementation demonstrated early adoption of maggot cultivation at the household level. This program contributed to improving community knowledge, skills, and early behavioral changes in organic waste management. Furthermore, the intervention supports environmental sanitation improvement and local economic strengthening. Continuous monitoring and program expansion are recommended to ensure sustainability and scalability in similar contexts.